The role of the integrated stress response in lovastatin induced apoptosis - Niknejad, Nima (University of Ottawa (Canada), 2010)
Lovastatin, a competitive inhibitor of the mevalonate pathway, is commonly prescribed for the treatment of hypercholesterolemia. More recently lovastatin has demonstrated an ability to induce tumour specific apoptosis however the mechanism by which lovastatin exerts this activity is not well characterized. End products of the mevalonate pathway are critical for various cellular functions including N-linked protein glycosylation, tRNA production, and the prenylation of a wide variety of cellular proteins among them many GTP-binding proteins which regulate cell proliferation, intracellular trafficking, and cell motility. Blockade of the rate-limiting step of the mevalonate pathway by HMG-CoA reductase inhibitors such as statins, results in decreased levels of mevalonate and its downstream products and thus may have significant influences on many critical cellular functions. This study demonstrates that the loss of key downstream mevalonate pathway metabolites leads to the activation of the cellular stress response known as the integrated stress response regulating lovastatin induced apoptosis in sensitive cell lines including head and neck squamous cell carcinoma (HNSCC), SCC25. The integrated stress response (ISR) is a signaling pathway, activated in response to a variety of different cellular stresses, that induces a common set of genes involved in cellular signaling leading to phosphorylation and inactivation of translation initiation factor, eIF2-alpha. The expression levels of several known mediators of the ISR were studied at both transcriptional and translational levels in response to lovastatin treatment. Lovastatin treatment induced eIF2-alpha phosphorylation and inhibited global protein translation. ATF4 expression was also induced, as well as increased ATF3 and CHOP expression (targets ofATF4) in sensitive cell lines only. In CHOP (-/-) murine embryonic fibroblasts (MEFs), lovastatin-induced apoptosis was attenuated indicating a role for CHOP in this response. Furthermore, the eIF2-alpha kinase, GCN2, mediates induction ofATF4 and lovastatin-induced apoptosis was also attenuated in GCN2 (-/-) MEFs. Our analysis revealed that lovastatin induced cytotoxicity directly correlates with induction of ISR markers ATF4, CHOP and ATF3 in sensitive cell lines. ATF3 is a transcription factor with dual oncogenic or tumour suppressor roles within the context of carcinogenesis and depending on the stressor can be induced during the ISR. Examining the role ofATF3 within the lovastatin induced cell death revealed that expression ofGCN2 kinase and ATF4 are essential for its induction. In ATF3(-/-) MEFs, lovastatin-induced apoptosis was attenuated and induction of the pro-apoptotic transcription factor, CHOP, as well as its nuclear translocation was impaired. Consistently, depletion of atf3 mRNA in two different cancer cell lines confers them partial protection against lovastatin induced apoptosis. Our analysis shows that GADD34, a target gene of CHOP required for de-phosphorylation of eIF2-alpha, was also induced by lovastatin treatment and abrogating the function of GADD34 by means of salubrinal, a specific inhibitor ofGADD34 phosphatase activity, strongly enhanced cytotoxicity of low doses of lovastatin in MEFs and SCC25 cells and also strongly increased ATF3 expression levels. Therefore, combining mevalonate pathway inhibitors with agents that enhance the ISR represent a novel combinational therapeutic approach.
Keywords: Chemistry, Biochemistry.